Influence of nitrogen on grain qualities of fine rice genotypes in aman and boro seasons - Mannan, MA; Bhuiya, MSU; Hossain, SMA; Akhand, MIM (Bangladesh Journal of Agricultural Research, 2010)
Key Words: Influence of nitrogen; grain qualities; fine rice; aman; boro. DOI: 10.3329/bjar.v34i2.5806 Bangladesh J. Agril. Res. 34(2): 329-333, June 2009